Early approach and mixed treatment in schizophrenia management: Evidence-based clinical practice guideline from a specialized mental health public hospital in the Ministry of Health of Peru - Vílchez Salcedo, Luis Arturo (2019)
Introduction: Schizophrenia is a psychotic disorder characterized by substantive alteration of mental functioning and effects on the social functionality of affected individuals. Objective: Provide recommendations based on the best available evidence for early approach, pharmacological and psychosocial treatment. Methods: An Evidence-based Clinical Practice Guide (GPC-BE) was developed, adapted through a systematic, rigorous, transparent process, by a working group composed of methodologists and psychiatrists who are experts in the management of schizophrenia. The guide includes four clinical questions and recommendations, we searched for guides that respond to the prioritized topic, guides were pre-selected and evaluated using the “Appraisal of Guidelines for Research and Evaluation II” (AGREE-II) instrument, the one with the best methodological quality was chosen for adaptation. The systematic search for evidence for each clinical question was performed in multiple databases: MEDLINE / Ovid, EMBASE / Ovid, EMB reviews / Ovid. The selection and analysis of evidence was carried out using clinical pairs and methodologists, the recommendations were prepared using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Results: With the participation of the panel of clinical experts from institutes and hospitals in Peru in the management of schizophrenia, four recommendations were established for the early intervention, pharmacological and mixed treatment of adult patients with schizophrenia. Conclusions: The early approach of the first psychotic episode through community mental health centers (CSMC) and specialized hospitals and pharmacological treatment together with standardized psychosocial therapy is recommended. This article summarizes the evidence-based clinical practice guideline developed by a Peruvian public hospital specializing in mental health disorders.